Typical morphometric and geological characteristics of large-scale landslides in Central Nepal - Timilsina, Manita; Bhandary, Netra Prakash; Dahal, Ranjan Kumar; Yatabe, Ryuichi (Journal of Nepal Geological Society, 2012)
Available with full text.